Upaya Meningkatkan Pemahaman Siswa tentang Struktur Teks Pidato Melalui Metode Presentasi Antar Kelompok di Kelas IX B SMP Negeri 2 Arut Selatan Tahun Pelajaran 2020/202: Efforts to Improve Students' Understanding of Speech Text Structures Through Inter-Group Presentation Methods in Class IX B SMP Negeri 2 Arut Selatan Academic Year 2020/2021 - Darmawati, Darmawati (Anterior Jurnal, 2022)
Speech text is a form of one-way communication in the form of expressing thoughts and ideas from the speaker about something to many people. This classroom action research was conducted at SMP Negeri 2 Arut Selatan, in Class IX with 35 students. The procedure of this research is divided into two stages, namely the preparation stage and the research implementation stage. At the implementation stage, it is divided into several cycles, each cycle consists of four stages, namely planning, implementation/action, observation, and reflection. In the first cycle, students still look confused with their assignments in class, this can be caused by the presentation method. With effort and students in the hope of increasing the achievement of better student learning outcomes. The results of the understanding of the first cycle have obtained a score of 131, meaning that students' understanding of the structure of the speech text was good, and the number of students who had completed learning was 28 while the average class of the first cycle was 75.79. learning material increased compared to the previous cycle so it can be said that students are increasingly understanding with the use of the presentation method by students. The results of the second cycle of understanding obtained a score of 174 which means that students' understanding of the structure of the speech text is very good, and the number of students who have completed learning is 35 while the average class of cycle II is 80.48.